To compare the haemodynamic stress response of direct laryngoscopy and oro-tracheal intubation using McCoy and Macintosh blade in general anaesthesia - Maiti, Arupratan; Moitro, Sreya (Asian Journal of Medical Sciences, 2021)
Background: Direct Laryngoscopy and intubation lead to extensive stress response and sympathetic stimulation in the body which can be critical for some patient subsets like cardiac ischemia, raised intracranial tension, cerebral aneurysm, open globe injury, glaucoma etc. Hence reduction of the intense stress response is of utmost importance for a stable and safe hemodynamics in those patients. Aims and Objectives: 1. To find out the hemodynamic stress response exerted by the Macintosh blade and McCoy blade. 2. To compare the hemodynamic stress responses between the two blades. Materials and Methods: In this study we had selected 60(male and female in equal number) ASA grade-1 and grade- 2 patients posted for elective general surgery. They were randomly divided into two groups - group 1(laryngoscopy done by McCoy blade)and group 2(laryngoscopy done by Macintosh blade). Systolic Blood Pressure, Diastolic Blood Pressure , Mean Blood Pressure and Heart Rate were recorded before and after anaesthesia induction, just after intubation and one, three and six minutes after orotracheal intubation. Results: The results were compared over time between the two groups. Mean values of Systolic Blood Pressure, Diastolic Blood Pressure, Mean Blood Pressure and heart rate were significantly higher in group 2 as compared to group 1(with p values as 0.009, 0.008, 00.004 and 0.000 respectively). Conclusion: Thus we conclude that the stress response was significantly higher when laryngoscopy was done with Macintosh blade as compared with McCoy blade. We would also like to stress that the art of laryngoscopy should just not be mastered but all anaesthesiologists should think of and practise techniques which would make laryngoscopy smooth and less stressful for our patients. Intubation with McCoy laryngoscope blade is one such technique.